Neurospora crassa genetic maps and mapped loci - David D Perkins (Fungal Genetics Reports, 2000)
Maps. Loci are displayed only if their order is established with reasonable certainly, either from meiotic crossing over in multiple-point crosses, from duplication coverage, or by physical mapping Loci are not displayed but are listed below the maps if their order is uncertain relative to the loci that are shown, except that closely linked loci may sometimes be shown in parentheses on the map even if their relative order is unknown. Evidence for linkage is given in the lists and is referenced in the new compendium (Perkins, Radford, and Sachs 2000 Chromosomal Loci of Neurospora crassa. Academic Press). Crossover values and interval lengths are approximations. Numbers on which they are based are often small and the various stocks used for mapping differ in genes that affect meiotic recombination. Linkage group I is estimated to be at least 200 map units long and the total for all seven groups probably exceeds 1000.